Hannah Arendt's Critique of the Judenräte in Context: Modern Jewish Leadership and Radical Democracy. (27th August 2018) - Lederman, Shmuel
Abstract: Hannah Arendt's critique of the Judenräte (Jewish Councils) famously sparked a major controversy after her 1963 publication of Eichmann in Jerusalem . This article locates Arendt's position in the context of her earlier thinking about modern Jewish leadership and conceptions of leadership in Western political thought. Both themes demonstrate her longstanding radical democratic leanings. Thus, this article shifts our understanding of Arendt and the Judenräte beyond the narrow limits to which the debate has largely been confined.